Identifikasi Borneo Vortex Terhadap Dinamika Suhu Permukaan Laut di Laut Jawa - Yosafat Donni Haryanto; Shanas Septy Prayuda; Rezfiko Agdialta; Nelly Florida Riama; Agus Hartoko; Sutrisno Anggoro; Muhammad Zainuri (Jurnal Penelitian Sains, 2020)
The event of Borneo Vortex is a disruption of the synoptic scale that occurs when the Asian monsoon is active. Borneo Vortex occurs because of the interaction of the Asian monsoon winds with the wind from the southeast in the northwest region of Borneo so that the vortex is formed which can increase rainfall. Related with rainfall, Sea Surface Temperature (SST) becomes one of the factors that influence it. The purpose of this study is to examine the effect of Borneo Vortex on the dynamics of Sea Surface Temperatures in the Java Sea. The impact of Borneo Vortex, SST parameter becomes dynamic and very important to influence the condition of waters in Java Sea. Data used in this research is ERA Interim ECMWF (European Center for Medium-Range Weather Forecast) Reanalysis data in the form of wind component u and v, vortisitas relative, divergence, and specific humidity. Rainfall analysis is done using daily rainfall data of 3B42RT TRMM (Tropical Rainfall Measuring Mission), while SST data uses the data of Visualize NOAA (National Oceanic and Atmospheric Administration) High Resolution Blended Analysis Data. The Sea Surface Temperature analysis was performed using Remote Sensing data from the period of December until February (DJF) 2004/05 to 2014/15. The method used is to find the composite value of each parameter at the time of Borneo Vortex event during the time of research. The results identify that the largest event of Borneo Vortex was in December. With the presence of Borneo Vortex, there is a significant change in vorticity, divergence, moisture transport, rainfall, and SST. The impact of Borneo Vortex can increase rainfall and increase SST in the Java Sea. Borneo Vortex occurred in December January February at the time of an active Asian monsoon in northwest Borneo where there is a synoptic scale disorder in the form of a massive air vortex causing an increase in rainfall and the dynamics of SST tend to rise as well.Keywords: Borneo Vortex,  Java Sea,  Sea Surface Temperature.